2009
DOI: 10.1158/1078-0432.ccr-08-2954
|View full text |Cite
|
Sign up to set email alerts
|

In vitro and In vivo Radiosensitization with AZD6244 (ARRY-142886), an Inhibitor of Mitogen-activated Protein Kinase/Extracellular Signal-regulated Kinase 1/2 Kinase

Abstract: Purpose: The mitogen-activated protein (MAP) kinase pathway is important for cell proliferation, survival, and differentiation, and is frequently up-regulated in cancers. The MAP kinase pathway is also activated after exposure to ionizing radiation. We investigated the effects of AZD6244 (ARRY-142886), an inhibitor of MAP kinase/extracellular signal-regulated kinase 1/2, on radiation response. Experimental Design: The effects of AZD6244 on the in vitro radiosensitivity of human cancer cell lines (A549, MiaPaCa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
74
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(80 citation statements)
references
References 29 publications
(35 reference statements)
3
74
0
Order By: Relevance
“…Markers for DNA damage (phosphorylated H2AX) and apoptosis (cleaved caspase-3) were assessed by immunohistochemistry after 5 days of treatment, but did not reveal any significant difference between the combination and other groups (data not shown). This is consistent with other recent data, which also suggested that the interaction between AZD6244 and radiotherapy was independent of the effects on DNA double-strand break repair (from examining phosphorylated H2AX) or apoptosis (quantified with an Annexin V binding assay), but may correlate with an increase in mitotic catastrophe (45). However, unlike the Ras mutant cell lines in the study of Chung et al (45), AZD6244 alone or in combination with radiotherapy had no effect on the cell cycle profile of Calu-6 cells (data not shown).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Markers for DNA damage (phosphorylated H2AX) and apoptosis (cleaved caspase-3) were assessed by immunohistochemistry after 5 days of treatment, but did not reveal any significant difference between the combination and other groups (data not shown). This is consistent with other recent data, which also suggested that the interaction between AZD6244 and radiotherapy was independent of the effects on DNA double-strand break repair (from examining phosphorylated H2AX) or apoptosis (quantified with an Annexin V binding assay), but may correlate with an increase in mitotic catastrophe (45). However, unlike the Ras mutant cell lines in the study of Chung et al (45), AZD6244 alone or in combination with radiotherapy had no effect on the cell cycle profile of Calu-6 cells (data not shown).…”
Section: Discussionsupporting
confidence: 93%
“…5B). Chung et al (45) also observed an enhanced radiotherapeutic response in vivo when a single dose of AZD6244 (50 mg/kg) was administered 4 hours before a single dose of radiotherapy (3 Gy).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…42 Moreover, recent findings suggest a functional role for MEK1/2/ ERK1/2 in cell-cycle checkpoints. 43,44 However, the MEK1/2/ ERK1/2 pathway also mediates multiple survival functions, including down-regulation of proapoptotic proteins such as Bad and Bim. 45 The latter protein, implicated in potentiation of Chk1 inhibitor lethality by inhibitors of the Ras/MEK1/2/ERK1/2 pathway in the bulk population of MM cells, 20 also plays a functional role in the lethality of these regimens toward quiescent (G 0 /G 1 ) MM cells.…”
Section: Discussionmentioning
confidence: 99%
“…In an LPS-induced acute lung injury mouse model, pretreatment of mice with U0126 significantly reduced lung neutrophilia and diminished levels of TNF-alpha and chemotactic MIP-2 and killer cells in bronchoalveolar fluid, suggesting that the pharmacologic inhibition of ERK provides a promising new therapeutic strategy for lung inflammatory diseases [48]. Currently, some ERK pathway inhibitors, such as PD184352, PD0325901 and AZD6244, are being evaluated in clinical trials [49]. Other research results indicate that the ERK pathway inhibitor BAY43-9006 displays a very promising future in the treatment of cancer [50].…”
Section: Clinical Applications Of the Inhibitors Targeting Map Kinasementioning
confidence: 99%